Technical and economic analysis of retrofitting concentrated solar collector to generate the thermal energy required for the crude oil products distillation process - Saif W. Mohammed Ali; Hussam H. Jabbar; Abbas K. Alshaibany (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Recently, most oil companies are working to reduce the cost and carbon emissions accompanied crude oil distillation process by developing suitable sustainable technologies. The present work studies the viability of retrofitting concentrated solar collector (CSC) represented by parabolic trough collector (PTC) through the crude oil distillation process in three stages; crude oil preheating in a furnace, live steam injection, and the reboiler heater. The whole oil distillation unit and the PTC unit are modeled and solved using an American software called COCO V 3.6.0.13 and SAM 2022.11.21 (System Advisor Model). Three different working fluids are investigated through the study: therminol VP-1, hitech solar salt, and pressurized water at different mass flow rates. Additionally, the proposed system was analyzed economically using levelized cost of energy (LCOE) method. The required land area for the solar unit is analyzed through the study too. It was found that hitec solar salt requires higher input flow rate than the other heat transfer fluids (HTF) where the maximum flow rate reaches about (75 kg/s) while the minimum flow rate was found for pressurized water as the flow rate value reaches about (25.7 kg/s). It was found also that the maximum required thermal energy is the energy exhausted in the furnace for crude oil preheating process, and the minimum value is the energy required for steam generation. The economic feasibility study shows that retrofitting such a solar units would be more beneficial in the years period between 2022-2050 as the LCOE of flue gas (0.0363 $/kWh) is higher than the LCOE of PTC (0.01604 $/kWh) leading to an overall cost saving reaches about 14523013 $ after year of 2021. The land area analysis shows that the required area is increasing linearly in a rate of (0.62 kW/m2). The validation with recorded data from literature shows a good agreement in compare with the current work.